AESTHETIC MESOTHERAPY: NEW PROTOCOLS AND POSSIBILITIES OF INDIVIDUALIZATION OF TREATMENT - Amina Ibragim (Modern American Journals, 2025)
The article discusses modern approaches to aesthetic mesotherapy, including the use of innovative drugs, combined protocols and personalized treatment regimens. The mechanisms of action of mesotherapeutic cocktails, new directions (peptides, exosomes, biorevitalizants), as well as the role of individualization in increasing the effectiveness and safety of procedures are analyzed. Particular attention is paid to the clinical aspects and prospects for the development of this area in aesthetic medicine.
Keywords: Mesotherapy, aesthetic medicine, individualization of treatment, peptides, biorevitalization, exosomes.